Angiographic factors influencing the success of endovascular treatment of arteriovenous malformations involving the corpus callosum. (12th August 2014) - Robert, Thomas; Blanc, Raphaël; Ciccio, Gabriele; Gilboa, Boaz; Fahed, Robert; Redjem, Hocine; Pistocchi, Silvia; Bartolini, Bruno; Piotin, Michel
Abstract : Objective: Arteriovenous malformations (AVMs) of the corpus callosum are rare lesions, accounting for 9–11% of brain AVMs. Microsurgical resection of such lesions is difficult because of their deep location, and also because of possible neuropsychological disasters resulting from extended callosal resection. The introduction of endovascular and radiation therapies has fundamentally changed the outcome of these lesions. Methods: We prospectively collected clinical and angiographic data on cerebral AVMs from 1995. We reviewed data from patients treated for an AVM of the corpus callosum and identified the factors influencing the endovascular approach of such lesions. Results: 38 patients (mean age 31 years) were consecutively treated by endovascular techniques. 78.9% (30 cases) of patients presented with intracranial hemorrhage. 15 AVMs (39.5%) were anterior, 18 (47.4%) were posterior, and five (13.1%) were holocallosal. The Spetzler–Martin grade was I in two cases (5.2%), II in 20 cases (52.6%), III in nine cases (23.7%), IV in six cases (15.8%), and V in one case (2.6%). The nidus was compact in 19 cases (50%), diffuse in 13 (34.2%), and multifocal in six (15.8%). Both anterior and posterior circulation branches fed 14 nidi (36.8%). Venous drainage was superficial in three cases (7.9%), deep in 28 (73.7%), and both in seven cases (18.4%). 104 sessions were performed, with a procedural complication rate of 6.7%. Mean follow-up was 43.6 months, with the last modified Rankin Scale score <3 in 33 cases (86.8%). 22 patients (57.9%) were totally cured. Univariate analysis of factors influencing the success of endovascular treatment showed that Spetzler–Martin grade ≥3 (p=0.046), nidus >30 mm (p=0.02), extension in an eloquent area (p=0.03), and holocallosal type (p0.005) significantly diminished the chances of cure of the AVM. Conclusions: AVMs of the corpus callosum seems to be difficult to treat with endovascular therapy alone. The goal of embolization should be prevention of (re) bleeding and a decrease in nidus size. Our experience regarding this sub-pathology suggests that a combination of endovascular therapy and radiotherapy may be the best option.